PASANG SURUT KEBIJAKAN DAN KINERJA PEMBANGUNAN DI KOTA BANDUNG DALAM ERA OTONOMI LUAS - W. Utomo, Tri Widodo (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2004)
Decentralization is widely believed to be an effective tool for promoting democratic local governance as well as a cure for bureaucratic pathology. Based on literature studies and,cross-country evidence, policy on regional autonomy promises many significant improvements in varying sectors of development. In the case of Law 22/1999, however, it does not produce expected results yet, both at local and national levels. This paper examines the correlation between decentralization framework and socio-economic development in Bandung, with special reference to the six development fields, i.e. budget management, investment, physical infrastructure, education and human development, environmental protection, and people participation and community development. The general conclusion is that there are many significant changes but only little progress. This might be caused either by incorrect implementation or insufficient time to implement the law. Whatever the causes are, this paper supports the idea of revising some parts of the law in order to create a better atmosphere of local politics.